Hemosuccus Pancreaticus Due to a Noninflammatory Pancreatic Pseudotumor - Cerrato, Darling Ruiz; Beteck, Besem; Sardana, Neeraj; Farooqui, Saleem; Allen, Danisha; Cunningham, Steven C (JOP. Journal of the Pancreas, 2014)
Context Hemosuccus pancreaticus is a rare source of gastrointestinal bleeding, the most frequent cause of which is pancreatitis, followed by tumors, but nearly all these tumors are true neoplasms, and not pseudotumors. Furthermore, nearly all pseudotumors of the pancreas and retroperitoneum are inflammatory. Case report We present a case of hemosuccus pancreaticus associated with a nonneoplastic noninflammatory pseudotumor of the pancreas. Conclusions Pancreatic pseudotumors are not always inflammatory and should be considered in the differential diagnosis of gastrointestinal bleeding associated with hemosuccus pancreaticus. Image: View at EGD, with gross blood emanating from major papilla.